Strategies Adopted to Achieve Competitive Advantage of Commercial Banks in Nakuru County, Kenya - Kibebe M’mbwanga, Sonia; Anyieni, Abel (International Journal of Scientific Research and Management (IJSRM), 2022)
Commercial banks carry out a particularly critical role in an economy’s progression and development. As such, a banking sector that is competitive strengthens economic stability and efficiency, promoting social welfare by way of offering financial services and allocating funds to firms and households. The recent collapse of three large commercial banks in Kenya and their ensuing placement on receivership and liquidation highlight the inadequacies by commercial banks in the country to formulate and adopt strategies that at aim at not only ensuring a sufficient customer-base that translates to core deposit growth but also competitiveness and eventually competitive advantage. Against this backdrop, the study set out to assess competitive advantage among commercial banks is influenced by strategic adoption with a focus on Nakuru County, Kenya. Anchored on the resource-based view and dynamic capability theories, the study took the descriptive survey research design, targeting 68 bank operations and branch managers from the 34 commercial Banks in Nakuru Town. These were reached on census survey approach, utilizing primary data collected by use of questionnaires that are structured in design. Descriptive statistics were analysed using frequency counts, percentages, and means. Inferential statistics were analysed using regression model. The study employed regression analysis to assess the association between the predictor and outcome variables. Findings show that firm infrastructure, human resource management, and technology are significantly associated with commercial banks’ competitiveness in Nakuru County, while procurement practices are not. It is concluded that firm infrastructure, human resource management, and technology have a significant effect on commercial banks’ competitiveness in Nakuru County while procurement practices do not. The study recommends that commercial banks seeking to improve their competitive advantage in the country should invest in adequate firm infrastructure, high performance human resource management practices, pertinent technology and in proper procurement practices.